The influence of the introduction of national guidelines on preterm birth prevention practice: UK experience. (28th December 2018) - Care, A; Ingleby, L; Alfirevic, Z; Sharp, A
Abstract : Objective: To identify the current status of specialist preterm labour (PTL) clinics and identify changes in management trends over the last 5 years following release of the NICE preterm birth (PTB) guidance. Design: Postal Survey of Clinical Practice. Setting: UK. Population: All consultant‐led obstetric units. Methods: A questionnaire was sent by post to all 187 NHS consultant‐led obstetric units. Units with a specialist PTL clinic were asked to answer a further six questions defining their protocol for risk stratification and management. Main outcome measures: Current practice in specialist PTL clinics. Changes in treatment trends over 5 years. Results: Thirty‐three PTL prevention clinics were identified, with 73% running weekly. NHS staff (84%) have replaced university staff as the lead clinicians (from 69% in 2012 to 21% in 2017), suggesting this clinic has become increasingly integrated with standard care for women at the highest risk of PTB. There has been a large shift from nearly half of clinics offering cerclage as primary treatment for short cervix to offering more choice (30%) between at least two of cerclage, vaginal progesterone or pessary and combinations of primary treatments (18%), demonstrating more equipoise among clinicians regarding therapies for short cervix. Conclusions: Over 5 years, there has been a 44% increase in the number of specialist PTL clinics in the UK. Although there is a better consensus over the target high‐risk population, there is increasing heterogeneity among first‐line treatments for short cervix. Tweetable abstract: UK PTB prevention clinics have increased by 44% over 5 years, with increasing clinical equipoise to best Rx for short cervix. Tweetable abstract: UK PTB prevention clinics have increased by 44% over 5 years, with increasing clinical equipoise to best Rx for short cervix.